Regulating vehicular emissions in three Asian cities comparative analysis of regulatory program design - Delfin, Francisco G., Jr (Philippine Journal of Public Administration, 2004)
Regulations governing vehicular emmissions in Delhi, Manila and Taipei are compared to examine how policymakers in democratic Asian cities anticipate compliance from target populations. Despite significant variations in their history and policy contexts, there is considerable similarity in the design of the three programs. The comparative analysis supports the Cohen and Kamieniecki (1991) strategic planning framework that states that size of the target population and the resources of the regulating agency affect compliance. Two additional elements are suggested which can affect compliance - dispersion of authority (Manila) and regulator' ownership of the program (Delhi). Economic climate in the outside arena does affect the choice of regulatory tools but not in the direction implied by Cohen and Kamieniecki. Costliness to implement coercive tools appear more common in the poorer Manila and Delhi compared to well-off Taipei. The article suggests that such trend may be due to: 1) policymakers in developing nations discounting economic climate as a major criterion when planning regulatory approaches, 2) reliance on command-and-control measures in relatively poor countries arises not out of cost consideration but out of tradition, and 3) market-based incentives as a regulatory tool may be conducive only to certain societies that have reached a relatively advanced level of economic development.